PERAN PERCEIVED AUTHENTICITY DALAM MEMEDIASI STRATEGI STORYTELLING DAN NILAI BUDAYA LOKAL TERHADAP LOYALITAS KONSUMEN DODOL GARUT - Sudirman, Sudirman; Susilawati, Wati; Cupiadi, Hedi (Penerbit Lafadz Jaya, 2026)
Dodol Garut is a traditional culinary product that represents regional identity and serves as an icon of the creative and tourism industries in West Java. This study aims to examine the mediating role of perceived authenticity in the relationship between storytelling strategies, local cultural values, and consumer loyalty. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that storytelling strategies significantly influence consumer loyalty both directly and indirectly through perceived authenticity. In contrast, local cultural values do not directly affect consumer loyalty but have a significant indirect effect through perceived authenticity. These results highlight that cultural values alone are insufficient to build loyalty unless they are transformed into perceived authenticity through effective narrative communication. This study contributes to culture-based marketing literature by positioning perceived authenticity as a key mediating mechanism in fostering consumer loyalty in traditional culinary products.